2022
DOI: 10.3346/jkms.2022.37.e321
|View full text |Cite
|
Sign up to set email alerts
|

Seeing Is Believing: The Effect of Graphical Abstracts on Citations and Social Media Exposure in Gastroenterology & Hepatology Journals

Abstract: Background Graphical abstracts (GAs) have recently been included as an essential element in various journals, including those in the field of Gastroenterology & Hepatology. However, there has been no study on the effect of GAs on the impact factor (IF) of journals, and the citation index or social media exposure of individual articles. Methods We investigated the presence of GAs, total citations and social media exposure of full-length original articles in the top ten j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 21 publications
2
7
1
Order By: Relevance
“…According to a study published by Yoon et al [9] in 2017, the number of journals adopting the GA system increased by 350% from 2011 to 2015, a trend also evident in the fields of geography, sociology, psychology, economics, and political science. The same phenomenon was also observed in Korea: ever since the Journal of Korean Medical Science introduced the GA system in Korea, more than 10 medical SCIE journals based in Korea have introduced the GA system from 2021 to 2022, including the Korean Journal of Internal Medicine [13].…”
Section: Definition and History Of Gassupporting
confidence: 61%
See 1 more Smart Citation
“…According to a study published by Yoon et al [9] in 2017, the number of journals adopting the GA system increased by 350% from 2011 to 2015, a trend also evident in the fields of geography, sociology, psychology, economics, and political science. The same phenomenon was also observed in Korea: ever since the Journal of Korean Medical Science introduced the GA system in Korea, more than 10 medical SCIE journals based in Korea have introduced the GA system from 2021 to 2022, including the Korean Journal of Internal Medicine [13].…”
Section: Definition and History Of Gassupporting
confidence: 61%
“…According to the aforementioned study on online engagement, healthcare professionals interacted more actively with the inclusion of a GA rather than an abstract or an article title (45.3 times vs. 29.4 times or 28.8 times, respectively). The effect of GAs encouraging online engagement in social media has been confirmed in several medical disciplines, including orthopedics, nephrology, psychiatry, and gastroenterology [13,[17][18][19].…”
Section: Are Gas Really Effective In Increasing the Dissemination Or ...mentioning
confidence: 93%
“…The effect of GAs on citation counts is unclear, largely due to the conflicting results presented in the research, with some studies reporting a negative association (Aggarwal, 2021;Bennett & Slattery, 2022;Pferschy-Wenzig et al, 2016), the present study no association, and one a positive association (Kim et al, 2022). Why GAs would have a negative effect on citations is unclear, but Pferschy-Wenzig et al ( 2016) provided potential explanations (Pferschy-Wenzig et al, 2016).…”
Section: Discussionmentioning
confidence: 63%
“…A recently published pre-print using a cross-sectional design demonstrated that articles published with a GA were associated with lower Altmetric attention scores and citations counts than those published with a GA in three high ranking sport science journals (Bennett & Slattery, 2022). Lastly, Kim et al (2022) found that articles published with a GA in the top ten journals in the fields of gastroenterology and hepatology were associated with higher Altmetric attention scores and citations than those published without (Kim et al, 2022).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation